"Every little thing that could possibly be provided helps": analysis of online first-year chemistry resources using the universal design for learning framework. Issue 2 (6th January 2022) - Reyes, Charisse T.; Lawrie, Gwendolyn A.; Thompson, Christopher D.; Kyne, Sara H.
Abstract : Rapid advancements in information and communication technologies (ICTs) have afforded numerous variations to traditional chemistry curricula where pedagogical strategies that have been employed have assumed "one-size-fits-all". The translation of print-based instructional resources into multimodal online and digital forms enables greater accessibility, flexibility, and usability to support students in their understanding of complex chemistry concepts. To ideally offer an online learning environment that is accessible by all students to the greatest extent possible, this study employed the principles of the Universal Design for Learning (UDL) framework to analyse the design of online instructional resources for topics in first-year chemistry courses. Through application of UDL principles, students were provided with multiple means of representation of concepts, options for action and expression, and various avenues for engagement within the learning management system (LMS). This paper describes how the UDL framework was used to evaluate three separate independent Cases of tertiary first-year chemistry courses, including one university in the Philippines and two universities in Australia. Evaluation through surveys, focus groups, and individual interviews revealed students' perceptions of the usefulness of the UDL-based features. Students cited benefit from multiple forms of content delivery, animations, interactive simulations, and video recordings because they facilitated processing of information, provided alternative ways of presenting the information, allowed for varying methods for response, navigation, and flexibility, and allowed for self-evaluation of their progress. These results suggest that applying the principles of the UDL framework in instructional design of an online environment in first-year chemistry courses can support and further enhance students' learning irrespective of their individual contexts.